2011
DOI: 10.1002/em.20659
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the genotoxic and cytotoxic effects of artesunate, an antimalarial drug, in human lymphocytes

Abstract: Artesunate is one of the main antimalarial drugs used in several countries. It is a semisynthetic compound derived from artemisinin, a substance extracted from the Chinese plant, Artemisia annua L. Despite the widespread use of artesunate as an antimalarial drug, there is a lack of data regarding its genotoxic effects in human lymphocytes. Therefore, in this study, we used the comet assay and micronucleus test to evaluate the possible genotoxic effects of artesunate in cultured human lymphocytes. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…Artesunate, is a derivative of artemisinin isolated from Artemisia annua L, has been used to treat malaria, especially against cerebral malaria (Padilla-Camberos et al, 2010;Bachmeier et al, 2011;Berdelle et al, 2011;Jin et al, 2011;Mota et al, 2011;Jiang et al, 2012;Zhou et al, 2012), new report shown that it has a variety of biological activities, such as hepatoprotective, antioxidative, antiinflammatory, antidiabetic, antiallergic, and antibacterial effects (Li et al, 2009;Bat-Chen et al, 2010;Du et al,…”
Section: Introductionmentioning
confidence: 99%
“…Artesunate, is a derivative of artemisinin isolated from Artemisia annua L, has been used to treat malaria, especially against cerebral malaria (Padilla-Camberos et al, 2010;Bachmeier et al, 2011;Berdelle et al, 2011;Jin et al, 2011;Mota et al, 2011;Jiang et al, 2012;Zhou et al, 2012), new report shown that it has a variety of biological activities, such as hepatoprotective, antioxidative, antiinflammatory, antidiabetic, antiallergic, and antibacterial effects (Li et al, 2009;Bat-Chen et al, 2010;Du et al,…”
Section: Introductionmentioning
confidence: 99%
“…These authors also concluded that in mammalian cells, artesunate generated damage through direct or indirect oxidative stress, resulting in DNA strand breakage. Mota et al (2011) also reported the genotoxicity of artesunate in human peripheral lymphocytes. The present study confirmed such genotoxicity in vitro for human metabolizing cells, and further studies are necessary to determine whether the generation of ROS could be involved in the genotoxicity of artesunate.…”
Section: Discussionmentioning
confidence: 99%
“…Aquino et al (2011) reported genotoxic effects of artesunate in liver cells of mice at low doses and clastogenic effects at high doses in bone marrow cells of the same animals. Li et al (2008) and Mota et al (2011) reported genotoxic and cytotoxic effects of artesunate in vitro in Chinese hamster ovary cells and in human peripheral lymphocytes, respectively. To the best of our knowledge, no genotoxic studies on mammalian cells of artemisinin and no genotoxic studies on metabolizing cells of artemisinin and artesunate have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Genotoxicity and cytotoxicity of artisunate were also studied by Mota et al, 52 in human lymphocyte. Comet assay and micronucleus test were used to evaluate the possible genotoxic effects of artesunate.…”
Section: Artimisininmentioning
confidence: 99%